Anaesthesiology and intensive care Does the optimization of intra-operative cerebral regional oxygen saturation have an effect on neurological function in elderly patients undergoing cardiac surgery? - Kucewicz, Ewa; Żegleń, Sławomir; Wojarski, Jacek; Głowacki, Jan; Borkowski, Jarosław; Leśniak, Konrad; Podwińska, Ewa; Skuza, Katarzyna; Puzio, Agata; Przybylski, Roman (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: The optimization of cerebral oxygen delivery variables by using noninvasive cerebral oximetry could reduce the incidence of stroke. The aim of the stud y was to evaluate the effect of the intraoperative management of oxygen delivery on neurological function during the early postoperative period in elderly patients undergoing cardiac surgery. Material and methods : This observational study included 257 patients, aged 75 and above, who underwent surgery in 2011. In the study group (119 patients), cerebral oxygen saturation was monitored and managed in order to maintain the oximetry values within individually assigned optimal levels. The control group (138 patients) underwent cardiac surgery without the intraoperative monitoring of cerebral oximetry. The two groups were dissimilar with regard to age, EuroSCORE risk factors, previous cerebral vascular accidents, and chronic kidney disease. More patients in the control group had preoperative NYHA class I. Results: There was no difference between the groups with regard to the incidence of permanent stroke. Total ventilation time was significantly shorter in the study group. Patients in the study group required shorter lung ventilation and a lower number of packed red blood cell units. The length of postoperative ward and hospital stay was longer among the patients with low values of baseline cerebral oximetry (< 50%). Conclusions: These findings suggest that intraoperative patient management based on cerebral oxygen monitoring may improve the postoperative course in elderly patients after cardiac surgery.